IMPLEMENTASI DAN PENGENDALIAN MUTU LEMBAGA PENDIDIKAN: Implementasi Strategi dan Pengendalian Mutu dalam Peningkatan Kualitas Pendidikan - Lulu Alwiyah; Darajat, Zulfa Awaliyah; Duryat, Masduki (CV. Media Publikasi Profesional, 2025)
Quality control is a key component in ensuring the sustainability and improvement of educational quality. This article aims to analyze the implementation of quality strategies, quality control processes, and the internal and external factors that influence the enhancement of educational quality. The study employs a descriptive qualitative method through a literature review, applying PRISMA principles to ensure transparency, traceability, and the rigor of the selected sources. The review process includes the identification, screening, eligibility assessment, and analysis of literature relevant to educational quality control. The findings indicate that quality improvement is inseparable from effective leadership, teacher competence, parental support, learning environment conditions, and the availability of adequate facilities. Furthermore, the integration of quality management, continuous evaluation, and a culture of ongoing improvement forms the essential foundation for achieving competitive and high-quality educational institutions. These results underscore that strengthening educational quality requires a systemic and collaborative approach involving all educational stakeholders.